Pengaruh Variasi Jenis Enzim dan Waktu Perendaman Pada Warna dan Kejernihan Gelatin Berbasis Tulang Ikan Bandeng Hasil Hidrolisis Enzimatis - Zulfatun Najah; Puji Wulandari; Nurul Annazhifah; Talitha Nur Aisyah Sahda; Fitriyani Fitriyani (Journal of Innovative and Creativity, 2026)
The purpose of the study was to determine the color characteristics and clarity of gelatin products resulting from enzymatic hydrolysis of milkfish bones with bromelain and papain enzymes. Materials and methods. The research methods were preparation, extraction, and hydrolysis. The experimental design was carried out with a split plot in the randomized block design consisting of two factors, namely the type of enzyme (Bromelain and Papain) and soaking time (12, 16, and 20 hours). Main material was fish bone from local industrial by products, enzyme. Data were analyzed for variance of analysis (ANOVA) and the DMRT test continued at a 1% significant level. Results. Color and clarity was product characteristics that affect consumer preference. The lightness value (L*) of fishbone gelatin was range from 25.75 – 55.03 where the brightness of bromelain gelatin (49.06 – 55.03) was higher than papain (25,74-34,73). The chroma value of gelatin from enzymatic hydrolysis of bromelain (25,11 – 25,63) is lower than papain (27,58 – 34,07). The clarity value of enzymatic hydrolysis-based milkfish bone was 0,30%. Conclusions. The type of enzyme had a very significant effect on color (lightness, a* value, b* value, and chroma value and clarity). Meanwhile, the soaking time has a very significant effect on color (lightness, a* value, b* value, chroma value, and clarity). There was interaction between both factors on color and clarity.